Pembatasan Penggunaan Gadget Pada Anak di Bawah Umur Dalam Menumbuhkan Kecerdasan Digital : Studi Kasus Desa Mojo Kecamatan Mojo Kabupaten Kediri - Mubayinah, Silvia; Mala, Asnal; Yusuf, Muhammad; Mukharomah, Novi Nur (Aktualisasi Pengabdian Masyarakat, 2025)
The use of gagdet among underage children has significantly increase in recent years with the advancement of the era. However, without a proper guidance and limits, the use of gadget can may lead to negative impacts that affect to the children’s cognitive and social development. This article aims to implement and educate children about the importance of limiting gadget in order to support the healthy and optimal development of digital intelegent. Through training programs, socialization, and direct assistance, this activity succesfully increased children’s awareness and digital skills, enabling them to use technology wisely and productively. The result of this program show that limiting screen time and monitoring appropriate content can help children develop beneficial digital skills while reducing excessive dependence on digital devices. With a participatory approach, the community can actively contribute to shaping digitally intelegent, responsible, and ethical young generation.